Talent Identification for Diving Sports Literature Review (Viewed from Biomotor) - Ilham Adi Wicaksono; Muhammad Yanuar Rizky; Reo Prasetiyo Herpandika (CV. Nusantara Sporta, 2024)
This research is motivated by the fact that there is still little research on the sport of diving involving biomotor aspects in athletes. As well as measuring physical data and ideal body size in talented athletes, it is a requirement for coaching in order to improve diving sports performance. This research aims to determine the biomotor components of the diving sport. This research uses a literature review. The data sources used in this research come from the results of research that has been carried out and published in national and international online journals. The data collection process is by using Google Scholar, Research and Gate, and Web of Science. The journals used were journals published in full text and indexed Sinta 1 to Sinta 5. The results obtained were 38 articles and 7 articles that met the inclusion criteria were then analyzed using quantitative descriptive analysis techniques. The conclusion of the results of this research is that the 7 articles agree that the anthropometric factors needed to identify talented athletes in the sport of diving are 7 measurements including endurance, speed, agility, flexibility, balance, strength, and reaction.